ANALYSIS OF FACTORS THAT DETERMINE CUSTOMER DELIGHT AND THEIR IMPACT ON CUSTOMER LOYALTY - I Wayan Oka Sugarda; I Nengah Suardhika; I Ketut Setia Sapta (International Journal of Applied Business and International Management, 2023)
Customers are the first asset that must be taken care of properly because each customer will bring profits that can keep the business running. Customers are kings who must be considered in every need and desire for the company's success in running its business. This study aimed to test and confirm the relationship between the variables of service quality, customer value, customer delight, and customer loyalty at Apotek Iwos Farma Badung. Respondents in this study were customers of Apotek Iwos Farma Badung. The number of respondents in this study was set at 80 respondents. This study uses structural equation modeling analysis with the help of the Smart-PLS 3 program. The results of this study indicate that the better the quality of existing services will be able to increase customer delight. Good customer value will be able to improve customer delight. The quality of existing services has not been able to increase customer loyalty. The higher the value of existing customers will be able to increase customer loyalty. However, customer delight has not been able to determine the increase in customer loyalty.